2002
DOI: 10.1002/gps.545
|View full text |Cite
|
Sign up to set email alerts
|

The effect of selegiline in the treatment of people with Alzheimer's disease: a meta‐analysis of published trials

Abstract: Although there was some evidence of improvement with selegiline in the short term in cognition and activities of daily living, the magnitude of the effect did not reach clinical importance. There was no evidence of long term effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…An example of this was illustrated by Jones et al using an IPD meta‐analysis of longitudinal data from five trials that investigated Selegiline versus placebo for the treatment of Alzheimer's disease 84, 86. The outcome of interest over time was the mini‐mental state examination, which is a measure of cognitive function.…”
Section: Key Reasons Why Meta‐analysis Results May Differ For the Onementioning
confidence: 99%
“…An example of this was illustrated by Jones et al using an IPD meta‐analysis of longitudinal data from five trials that investigated Selegiline versus placebo for the treatment of Alzheimer's disease 84, 86. The outcome of interest over time was the mini‐mental state examination, which is a measure of cognitive function.…”
Section: Key Reasons Why Meta‐analysis Results May Differ For the Onementioning
confidence: 99%
“…An increasing number of molecular biology and pharmacology studies have shown the neuroprotective effects of MAO inhibitors on the prevention and treatment of AD (21,52,53) (Table I) (15,56,57,61,62,112,114,(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142)(143)(144). The main neuroprotective mechanisms of MAO inhibitors in AD include the following: i) Improvement of cognitive impairment (50,54,55), where MAO inhibitors correct chemical imbalances in the brain; ii) antioxidant activities and enhancement of iron-chelating activities (56)(57)(58)(59), where chelators can modulate Aβ accumulation, protect against tau hyperphosphorylation and block metal-associated oxidative stress, thereby holding considerable promise as effective anti-AD drugs (145,146); iii) regulation of APP and Aβ expression processing (56,60), for example ladostigil (TV3326), a selective MAO-B inhibitor, which regulates APP translation and processing (114); iv) the selective MAO inhibitors selegiline and rasagiline have been proven to possess neuroprotective activities in cell cultures and animal models of neurodegenerative diseases through the activation of certain signaling pathways, including p42/44 MAPK and PKC (61); v) inhibition of ChE activity by the MAO inhibitor rasagiline (62)(63)…”
Section: Evidence For the Neuroprotective Effect Of Mao Inhibitors In Admentioning
confidence: 99%
“…Loss of neurons in the locus coeruleus seems to be a characteristic of AD that correlates with the severity of the dementia (Bondareff et al, 1982) and has not been reported in dementia caused by multiple infarcts (Mann et al, 1982). Deprenyl has been reported to briefly improve cognition in a clinical AD trial (Wilcock et al, 2002). Indeed, the combination of L-deprenyl and physostigmine, an AChE inhibitor, has been shown to be more beneficial in patients with AD than physostigmine alone (Schneider et al, 1993).…”
Section: Galantamine Enhances Nicotine-induced Norepinephrine Releasementioning
confidence: 99%